1985
DOI: 10.1079/bjn19850131
|View full text |Cite
|
Sign up to set email alerts
|

Insulin action and glucose metabolism in sheep fed on dried-grass or ground, maize-based diets

Abstract: I. The effect of an exogenous supply of glucose, provided by the digestion of maize starch in the small intestine, on endogenous glucose metabolism and insulin action was studied in sheep using the euglycaemic insulin clamp procedure.2. Insulin was infused intravenously at rates of 0.2, 0.5, 1.0 and 6.0 mU/min per kg live weight for four consecutive periods in each of four sheep fed on dried-grass and maize-based diets. Glucose was also infused intravenously at a variable rate, sufficient to maintain the plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
33
1
1

Year Published

1992
1992
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 29 publications
(28 reference statements)
8
33
1
1
Order By: Relevance
“…In the glucose clamp procedure, blood GTR increased with increased insulin infusion rates in a dose-dependent manner as reported previously [15,33,34]. This reflected enhanced glucose utilization in insulin dependent tissues such as skeletal muscle and adipose tissue [35].…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…In the glucose clamp procedure, blood GTR increased with increased insulin infusion rates in a dose-dependent manner as reported previously [15,33,34]. This reflected enhanced glucose utilization in insulin dependent tissues such as skeletal muscle and adipose tissue [35].…”
Section: Discussionsupporting
confidence: 56%
“…Sano et al [21] obtained a similar ratio to the present experiment in sheep. On the contrary, Janes et al [15] reported that in sheep, the EGPR was completely suppressed during the hyperinsulinemic euglycemic clamp procedure at 6 mU·kg -1 BW per min of insulin infusion. Bergman et al [33] also reported that in sheep, complete suppression of endogenous glucose appearance rate occurred at insulin concentrations of 50 to 300 μU·mL -1 .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Endogenous glucose production was suppressed by 30 to 60% and glucose utilization was stimulated by 0 to 30% when plasma insulin concentration was increased to twofold that of basal states by insulin infusion with a maintained plasma glucose concentration [29][30][31]. This suggests that the increase in plasma insulin concentration during the postfeeding period in the present study should produce a decrease in glucose entry and no change or a slight increase in glucose utilization.…”
Section: Discussionmentioning
confidence: 63%
“…However, the mechanism is unclear as well as that of a possible increase in insulin-independent glucose utilization with feeding. Research may be needed for elucidating the mechanism, because insulin-independent glucose utilization accounts for over 80% of total glucose utilization in ruminants in a basal state [29].…”
Section: Discussionmentioning
confidence: 99%